2019
DOI: 10.3390/w11091834
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Drought over the Northeast United States

Abstract: The Northeast United States is a generally wet region that has had substantial increases in mean precipitation over the past decades, but also experiences damaging droughts. We evaluated drought frequency, intensity, and duration trends in the region over the period 1901–2015. We used a dataset of Standardized Precipitation Evapotranspiration Index (SPEI), a measure of water balance based on meteorology that is computed at multiple timescales. It was found that the frequency of droughts decreased over this per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 76 publications
0
11
0
1
Order By: Relevance
“…The results of this study imply that the restoration of wetlands may play a role in the mitigation of climate change through the ability to store C that would otherwise be emitted as CO 2 . Additionally, we observed that GHG emissions and soil parameters were affected by drought conditions such as those experienced in Massachusetts in the summer of 2016 and that are predicted by climate change models to increase in frequency (Krakauer et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study imply that the restoration of wetlands may play a role in the mitigation of climate change through the ability to store C that would otherwise be emitted as CO 2 . Additionally, we observed that GHG emissions and soil parameters were affected by drought conditions such as those experienced in Massachusetts in the summer of 2016 and that are predicted by climate change models to increase in frequency (Krakauer et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The arithmetical mean of drought duration, severity, intensity, and peak is used to compare different zones. Several studies have used the run theory for the identification and characterization of droughts [18,19,21,23,41].…”
Section: Drought Characterizationmentioning
confidence: 99%
“…Therefore, SPEI reflects the effects of temperature on droughts, and so is more suitable for drought monitoring in a changing climate. There have been various studies conducted that show the efficiency of SPEI as an index to monitor and characterize droughts [14][15][16][17][18][19][20][21][22]. SPEI has also been documented to be a suitable indicator for monitoring droughts in Pakistan [14,23].…”
Section: Introductionmentioning
confidence: 99%